PKM PENGOLAHAN UBI JALAR MENJADI ES CENDOL - Nurjannah Nurjannah; Arisah, Nur; Subur, Hikmayani; Hasyim, Sitti Hajerah; Mustari, Mustari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
One of the Community Service activities that can increase the purchasing value of raw materials is cassava which is processed into cendol ice. Processing this product can increase community income with a home industry business or commonly called a home business in processing sweet potatoes into cendol ice. The methods used in this activity include lectures, questions and answers or discussions, and training. Training and mentoring were carried out in Pangkajene District, Pangkajene and Kepulauan Regency for 2 weeks. The results obtained were (1) The training on processing cassava into cendol ice was well responded by the participants; (2) The high interest and motivation of the training participants greatly supported the transfer of knowledge and skills from the service providers to the training participants, so that the training materials provided could be absorbed by all; and (3) The training product of processing cassava into cendol ice can be consumed daily and can be used as a community entrepreneurial product.